Islamic Education in Schools and Madrasas: Research Trend and Issues Based on Bibliometric Evidence - Edi Nurhidin; Maimunatun Habibah; Mohd Roslan Mohd Nor (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2025)
Islamic education studies are currently undergoing significant advancements in global publications. This study explores the progress in Islamic education publications across schools and madrasas through a bibliometric analysis. A keyword search in the Scopus database yielded 403 relevant publications from 2004 to 2023. Using the Bibliometrix R package, Biblioshiny, VOSviewer, and Microsoft Excel, we observed significant growth in this field. The journal